MDCT angiography of isolated right subclavian artery - Türkvatan, Aysel; Paç, Ayşenur; Kızıltepe, Uğursay; Ölçer, Tülay; Cumhur, Turhan (The Turkish Journal of Pediatrics, 2010)
Isolation of a subclavian artery is an uncommon congenital anomaly of the aortic arch in which one subclavian artery loses its connection with the aorta and originates from the homolateral pulmonary artery by way of a ductus arteriosus. Isolation of the left subclavian artery in patients with a right aortic arch is well known. However, isolated right subclavian artery with a left-sided aortic arch is an extremely rare condition. In this report, we present multidetector computed tomographic (MDCT) angiography findings of an isolated right subclavian artery associated with a common carotid trunk and an anomalous origin and proximal interruption of the left pulmonary artery.